COMPETITIVENESS IN THE SPHERE OF INNOVATIVE ENTREPRENEURSHIP - K. Yu. Reshetov; V. I. Mysachenko (Модернизация, инновация, развитие, 2016)
The theme of this article is relevant because in any economic doctrine of competition is seen as a driving force of the market. The ability of business entities, including entities of innovative entrepreneurship to compete for the market (consumers) is a key factor in the development of this segment and the main factor stimulating the transition of the national economy to innovation-oriented development.The purpose: The aim of the article is in-depth and comprehensive analysis of the positions of Russian and foreign scientists-economists on the question of the essence of the concepts of «competition» and «competitiveness».Methods. Methodological basis of this paper are generalization of literary sources and comparative analysis methods. Results. Comprehensively analyzed the positions of leading scientists and economists in relation to the concepts of «competition and competitiveness», including and in such an important sector as innovative entrepreneurship. The identifi ed similarities, diff erences and their features.Conclusions / significance. Identifi ed and completed a substantial part of the economic category «competitiveness of innovative entrepreneurship». According to the authors, the competitiveness of innovative entrepreneurship should be considered as the ability of the subjects of this segment to compete in a superior degree with the manufacturers (sellers) of a similar product (goods, works, services) with the best (unique) characteristics through effi cient and optimal use of knowledge and other resources to support the activities to maximize the economic benefi ts, not available to competitors of, or adjacent segment.